WRITING AND SELF CONSTRUCTION: a look at the trajectory of Carolina Maria de Jesus - Oliveira, Priscila (2023)
The purpose of this paper is to outline some elements that constitute the process of forming the person/writer Carolina Maria de Jesus beyond the work “Quarto de Despejo”, as opposed to a supposed alienation in terms of identification with a community or the sense of belonging of the “female, black, and peripheral” person/writer. To this end, we highlight certain biographical aspects of the author, and contextualise the environment of her production, taking into account the Brazilian socio-political scenario, especially that of the metropolis of São Paulo in the mid-twentieth century; however, these aspects should not be placed above the aesthetic and literary character of her overall work. We conclude that to access the creative power of the narrative and understand how Carolina Maria de Jesus was influenced, it is necessary to articulate both the perspective of decolonial studies and the critique based on the common ground of the so-called marginalised subjects’ practical experiences, whether class, race, or gender.